Light Weight Security Attack in Mobile Ad Hoc Network (MANET) - Muthukrishnan, H; Anandamurugan, S (International Journal of Computer Sciences and Engineering, 2014)
Mobile ad hoc network (MANET) is a collection of mobile nodes that communicate with each other without any fixed infrastructure or a central network authority. From a security design perspective, MANETs have no clear line of defense; i.e. no built-in security. Thus, the wireless channel is accessible to both legitimate network users and malicious attackers. Since MANET requires a unique, distinct, and persistent identity per node in order for their security protocols to be viable, Sybil attacks pose a serious threat to such networks. A Sybil attacker can either create more than one identity on a single physical device in order to launch a coordinated attack on the network or can switch identities in order to weaken the detection process, thereby promoting lack of accountability in the network. Here a lightweight scheme is used to detect the new identities of Sybil attackers without using centralized trusted third party or any extra hardware, such as directional antennae or a geographical positioning system. Through the help of extensive simulations, it is able to demonstrate that this scheme detects Sybil identities with good accuracy even in the presence of mobility.